2018
DOI: 10.20902/ijctr.2018.110737
|View full text |Cite
|
Sign up to set email alerts
|

Strain improvement, production and stability of Nattokinase from UV mutant strain of Pseudomonas aeruginosa CMSS

Abstract: Nattokinase (NK) is a potent fibrinolytic enzyme , which belongs to the second large family of serine proteases. NK gain significant attention in the treatment of hypertension and cardiovascular disorders (CVD's). Thus, a number of NK producers have been extensively studied, especially Pseudomonas sp. has extended the production level than Bacillus sp. with different properties. Thus the current study precedes with the strain improvement of NK producing UV mutated Pseudomonas aeruginosa CMSS by chemical mutage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…to control. EDTA and silver nitrate showed almost same amount of decrease in the enzyme activity as shown in fig16 and fig17. The statistical analysis done by ANOVA showed that there is no significant difference between the inhibitors used in Staphylokinase and Nattokinase production as p value was greater than 0.05 as shown in table 13..…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…to control. EDTA and silver nitrate showed almost same amount of decrease in the enzyme activity as shown in fig16 and fig17. The statistical analysis done by ANOVA showed that there is no significant difference between the inhibitors used in Staphylokinase and Nattokinase production as p value was greater than 0.05 as shown in table 13..…”
mentioning
confidence: 67%
“…It is produced by fermentation by adding the bacterium Bacillus natto which is the preeminent nattokinase producer (Haritha, M. et al, 2011). It is a serine protease of the subtilisin family with 275 amino acid residues and molecular weight of 27,728 Dalton having potent fibrinolytic activity (Mohansrinivasan, V. et al, 2014). Nattokinase is in expensive and promote normal blood pressure, reduce whole blood viscosity and increase circulation being an effective supplement to support cardiovascular disease (Kim, W. et al, 1996).…”
Section: Introductionmentioning
confidence: 99%